2016
DOI: 10.1111/bju.13465
|View full text |Cite
|
Sign up to set email alerts
|

Combination of prostate imaging reporting and data system (PIRADS) score and prostate‐specific antigen (PSA) density predicts biopsy outcome in prostate biopsy naïve patients

Abstract: ObjectiveTo assess the value of the Prostate Imaging Reporting and Data System (PI-RADS) scoring system, for prostate multiparametric magnetic resonance imaging (mpMRI) to detect prostate cancer, and classical parameters, such as prostatespecific antigen (PSA) level, prostate volume and PSA density, for predicting biopsy outcome in biopsy na€ ıve patients who have suspected prostate cancer. Patients and methodsPatients who underwent mpMRI at our hospital, and who had their first prostate biopsy between July 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
221
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(254 citation statements)
references
References 34 publications
29
221
1
3
Order By: Relevance
“…dPSA was the only non-MR variable included in this study. The fact that it consistently provided independent information to MR features is in line with a recent study that found that combining the PIRADS v2 score with dPSA improved prostate lesion characterization [43]. If the aim of scoring systems is to assess the likelihood of presence of csPCa, it might therefore be necessary to associate MR features and clinical or biochemical features in the future.…”
Section: Discussionsupporting
confidence: 65%
“…dPSA was the only non-MR variable included in this study. The fact that it consistently provided independent information to MR features is in line with a recent study that found that combining the PIRADS v2 score with dPSA improved prostate lesion characterization [43]. If the aim of scoring systems is to assess the likelihood of presence of csPCa, it might therefore be necessary to associate MR features and clinical or biochemical features in the future.…”
Section: Discussionsupporting
confidence: 65%
“…PI‐RADS category 3–5 warrant a repeat biopsy for patients with prior negative biopsies according to the American Urological Association and the Society of Abdominal Radiology . However, increasing evidence shows that lesions with PI‐RADS category 3 should be monitored without immediate biopsy to avoid unnecessary biopsy . In combination with additional clinical parameters, such as previous biopsy history, PV and PI‐RADS score, nomograms have yielded higher CSPC detection rates …”
Section: Introductionmentioning
confidence: 99%
“…In our study population, this would have resulted in a 20% decrease in the number of biopsies performed, and only 4% of significant cancers would have escaped diagnosis. If slightly different criteria suggested by other authors were applied to our cohort (i.e., PIRADS = 3 and PSAD < 0.15) [14,16,17], it would result in a 50% reduction in the number of biopsies but would also miss 21% of significant cancers. We speculate that the discrepancy between this finding and those reported in other papers might be explained by the performance of the mpMRI [3,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to our finding that 21% of biopsies could have been avoided using PIRADS < 3 and PSAD < 0.2 as the criteria for deciding not to perform a biopsy. Washino et al [14] reported that PIRADS ≤3 and PSAD < 0.15 ng/mL 2 identified no clinically significant PC on biopsy. They found that the PIRADS score and PSAD were both independent predictors of PC and of CSPC.…”
Section: Discussionmentioning
confidence: 99%